19 The benefits of an integrated eye clinic liaison officer in improving patient outcomes in ophthalmology. (December 2018) - Bacon, Jennifer; Coates, Hayley; Gupta, Nitin
Abstract : Introduction: The loss of sight can have a profound impact on a patient's independence and well-being. Giving patients the devastating news that they are losing their sight is very challenging and when receiving information, a patient often requires considerable support and time. Eye Clinic Liaison officers (ECLOs) are essential in providing patients, their families, and carers with practical and emotional support to help understand their diagnosis. They can help patients not only adapt to living with sight loss, but also to ensure they do not become isolated and retain their independence. ECLOs provide a vital role in bridging the gap between health and social care services, such as fall prevention, job retention, education and social services, enabling early intervention. The service demonstrates how health and social care can work together effectively and this supports the NHS outcomes framework. At the West Suffolk NHS Foundation Trust we have an integrated ECLO. This has proven to reduce DNA's, reduce clinician time per patient, help patient compliance with treatment, and streamline the process for sight registrations. The Royal college of Ophthalmologists recognised the importance of the role of ECLOs in 2007, in its guidelines to commissioners and clinicians, which recommended the use of ECLO's as part of Age-Related macular degeneration services. Methods: In order to investigate the aims and objectives, evidence was gathered from Ophthalmologists, Patients and other eye clinic staff, with satisfaction surveys filled by those whom accessed or referred patients to the ECLO service. Results: Surveys were collated and feedback was positive. Having an integrated ECLO has meant timely referrals to appropriate services, providing access to support, and also services such as low visual aids and mental health. Direct access to mental health services reduces the need for GP appointments, meaning that those who require help receive it sooner. Early falls prevention and referrals into the community team have reduced the number of falls for patients with visual impairment, reducing hospital admissions. 95% of surveys received from staff, working with ECLOs, said that it improved the patients experience and reduced time spent in the clinic. Patients felt happier that they were given time to discuss their eye conditions and have access to support. Other staff working within the Eye clinic also felt that they further understood sight loss after receiving visual awareness training. This training was also delivered to other professionals, including occupational therapists, within the hospital who have been better equipped to assist their visual impaired patients. Conclusions: The numbers of patients living with sight loss is gradually increasing the demand on ophthalmic services. Ophthalmic services continue to have the second highest number of outpatient attendances of any speciality, placing enormous pressure on ophthalmic staff to diagnose and treat patients. Having an integrated ECLO at the West Suffolk hospital has proved invaluable. The ECLO service is a good example of how integrated secondary care and social care improve patient outcomes. Evidence has shown that the service is well used and the ECLO service is a vital part of any Eye clinic.